Value of the dry ingredients and digestibility of Organic Goat nuts with the granting of Silage Rations of vegetable Trash and leaves Gliricidia (Gliricidia sepium) - Arwan, Arwan; Hafid, Harapin; Zulkarnain, Deki (Pascasarjana Universitas Sulawesi Tenggara, 2020)
This research aims to know the effect of vegetable silage ration feeding trash and leaves (Gliricidia sepium) gliricidia against the value of the dry ingredients and digestibility of organic livestock goat nuts. This study used a Randomized Design Group with 3 treatments and 3 replicates (blocks/groups) each of Deuteronomy includes 3 goats nuts. R1 is the treatment of gliricidia ad libitum leaves, vegetable waste and silage R1 leaves gliricidia (30%: 70%) and vegetable waste and silage R2 leaves gliricidia (70%: 30%). The observed variables are the values of the digestibility of dry ingredients and the digestibility of organic matter. The results showed that the treatment of vegetable waste silage given does not affect real (P0,05 >) against the consumption of dry ingredients of vegetable leaf litter silage ration gliricidia as a whole. The results showed equivalent value the digestibility of the ration dry ingredients of highest to lowest (%) respectively is R2 (80.7%), R1 (75,3%), and the Ro(71.3). While the addition of vegetable waste in silage ration leaves gliricidia does not affect real (P0,05>) against the value of the digestibility of organic matter. It can be concluded that the provision of rations of vegetable trash and leaves silage gliricidia (Gliricidia sepium) do not affect the real value of the dry ingredients and digestibility of organic livestock goat nuts.